1974
DOI: 10.1128/iai.10.6.1292-1295.1974
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Protects Mice Against Diplococcus pneumoniae Type I Infection

Abstract: Vitamin E protects nonimmunized and immunized mice against fatal Diplococcus pneumoniae type I (DpI) infection. A dietary supplementation of 180 mg of DL-a-tocopheryl acetate per kg of diet increased survival of nonimmunized mice from 20 to 80% when challenged with 20 organisms, and of mice immunized with 0.5 ng of DpI polysaccharide from 15 to 70% when challenged with 20,000 organisms. The phagocytic index of immunized mice was four times higher in the 180-mg vitamin E group than in the control group. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1976
1976
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 13 publications
(12 reference statements)
0
17
0
2
Order By: Relevance
“…Antioxidants, and vitamin E in particular, have been proposed to be beneficial against oxidative stress caused by heavy exercise, and while there are reports indicating benefit, the literature is quite divergent [13,19,25]. Vitamin E affects the immune system [15,17], and improves resistance to viral and bacterial infections in animals [5,6,17,27]. Under the assumption that physical activity causes oxidative stress which may harm the immune system, vitamin E could protect against these effects and thereby might influence the risk of infections.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants, and vitamin E in particular, have been proposed to be beneficial against oxidative stress caused by heavy exercise, and while there are reports indicating benefit, the literature is quite divergent [13,19,25]. Vitamin E affects the immune system [15,17], and improves resistance to viral and bacterial infections in animals [5,6,17,27]. Under the assumption that physical activity causes oxidative stress which may harm the immune system, vitamin E could protect against these effects and thereby might influence the risk of infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the mechanism involved in stimulating serum bactericidal activity in turtles is not presently clear, vitamin E may directly or indirectly play a role as a bactericide or bacteriostat. 9 In conclusion, dietary vitamin E significantly enhanced non-specific immune function in softshelled turtles, and the optimal dosage for improving blood cell phagocytosis, serum bacteriolytic activity, and bactericidal activity ranged from 250 to 500 mg/kg. This is the first report regarding the effects of vitamin E on serum bacteriolytic activity and bactericidal activity in a vertebrate species.…”
Section: The Effect Of Vitamin E On Serum Bactericidal Activitymentioning
confidence: 84%
“…Tengerdy et al (1978) showed that supplementation with 150-300 mgkg vitamin E significantly reduced E. coli-induced mortality in chickens (from 50% to 5%). Similarly, the mortality of mice infected with diplococcus pneumonia Type I decreased from 80 to 20% after vitamin E supplementation (Heinzerling et al 1974). The protective effect of vitamin E was associated with higher antibody titer, increased plaque forming units, and higher phagocytic activity.…”
Section: Infectious Diseasementioning
confidence: 91%